PENINGKATAN KEMAMPUAN MENULIS SURAT UNTUK TEMAN SEBAYA MELALUI PEMBELAJARAN KONTEKSTUAL DI SDN 04 BENGKAYANG - Tambal, Tambal; Marzuki, Marzuki; Syamsiati, Syamsiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the application of contextual learning in improving the ability to write letters for peers in primary school 04 Half Bengkayang. Research method used is descriptive, research form is class action research, research nature is collaborative. Subjects in this study were teachers and grade four students who numbered 17 students. Technique of collecting data in this research is direct observation and document observation. This study was conducted in three cycles. The results of the research are (1) The ability of the teacher in designing cycle I learning is 3.31 (good), cycle II is 3.39 (good) and cycle III is 3.59 (excellent). (2) The ability of the teacher to carry out the learning in cycle I is 3.19 (good), cycle II is 3.34 (good), and cycle III is 3.59. (3) Learning outcomes Writing Comprehension For Peer Friends by using contextual learning in Primary School 04 HalfBengkayang at cycle I is 71.87, cycle to II is 74.55 and cycle III is 80.53. Conclusion in this research is by using contextual learning can increase the ability to write letter for peer at SD 04, Bengkayang. Keywords: Ability to Write, Letters, and Contextual Learning.